Re-engineering Iraq [power production shortage]. - Zorpette, G.
This paper examines the reasons why, after three years of continuous support from the US government to reconstruct the electrical infrastructure in war-torn Iraq, there is still a shortage of about 4000 MW in the country's power production. The paper cites a variety of reasons that include the poor match between generating technologies and the kinds of fuels available in Iraq, the well-armed insurgency that has made destroying electrical infrastructure a centerpiece of its bid to destroy the country's fledgling democracy and the erosion of operational and, particularly, maintenance skills among workers at the country's Ministry of Electricity. With US funds available for new electrical projects dwindling into the hundreds of millions of dollars, the obstacles to a robust electricity supply system for all Iraqis are looming large.
Keywords: Iraq power production shortage; US government; Electrical infrastructure; Electrical infrastructure reconstruction; Electricity supply system; Generating technologies; Maintenance skills